Responding to the Psychosocial Experiences of First-Generation Master of Social Work (MSW) Students. Issue 1 (2nd January 2023) - Slates, Sarah; Moedano, Carmen
ABSTRACT: In this Notes From the Field essay, we bring together clinical practice and administrative experiences to explore and anticipate the psychosocial experiences of first-generation MSW students. Our goal is to offer programmatic suggestions that reflect the strengths and challenges of first-generation graduate students in social work programs and beyond. We begin by highlighting the unique psychosocial experiences of students with a mix of brief case vignettes illustrating themes shared in clinical practice. We then outline responsive programmatic approaches including entry, first-year, and ongoing student support services within a graduate school of social work.